Tindak Pidana Terorisme yang dilakukan oleh Anak Dibawah Umur - I Wayan Bayu Suryawan; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
This study aims to discuss the legal regulation of criminal acts of terrorism by minors and how the accountability of perpetrators of criminal acts of terrorism by minors is based on Law No. 15 of 2003 concerning the eradication of criminal acts of terrorism. This study uses a normative legal research type. Children are human resources who have a vital position in the development of the nation, but the phenomenon occurs that many children are involved and influenced by committing crimes of terrorism, where children are involved in criminal acts of terrorism. The results of the research on the legal regulation of criminal acts of terrorism committed by children have not been regulated by criminal provisions, they cannot be subject to capital punishment or life imprisonment. Cannot be held criminally responsible because there are conditions in the element of error that are not fulfilled, namely the requirement that those above a certain age can be held responsible. A child who has not been able to decide what he wants is said to be mentally immature, unable to make a decision correctly, even if the child commits a crime on his own consciousness. With the inability of children to be judged legally, special legal protection is needed for children.